AN ANALYSIS OF COHESION IN THE ABSTRACT OF THE THESES WRITTEN BY UNDERGRADUATE STUDENTS OF ENGLISH EDUCATION PROGRAM AT ONE STATE UNIVERSITY IN BANDUNG - Dania, Rahma (2016)
This study is an analysis of cohesion in the abstract of the theses written by undergraduate students of English education program at one state university in Bandung. Abstract is one of the important elements of the thesis. Therefore, the abstract must be written as a cohesive text, not just a collection of unrelated sentences. This study aims to explore the realization of cohesive devices in the abstracts of the theses written by undergraduate students of English Education Program at a state university in Bandung. This study also attempts to reveal the contributions of the cohesive devices used by the students in their abstract to build the cohesiveness of the text. This study belongs to a descriptive study involving 42 abstracts as the data of the study. This study exposes two main findings. First, cohesive devices that are employed in students' abstract are reference, conjunction, substitution, and lexical cohesion. Reference is the most prevalent device in all of the text, with 1156 occurrences. Second, each device gives significant contribution to the cohesiveness of students' abstract. Reference contributes to keep tract of the participants of the text and help readers to point to something within or outside the text. Lexical cohesion also contributes to keep tract of the participants of the text. Meanwhile, the contribution of conjunction in students' abstract is to connect the preceding part with the next one systematically. In addition, substitution is used by the students to avoid repetition in their abstract. Based on these findings, it can be concluded that cohesive devices are important devices to create cohesive abstracts. Without the devices, sentences would seem to lack connection to each other and might not be considered as a text (Halliday and Hasan, 1976). Therefore, it is recommended that a student who wants to write an abstract or particularly a whole thesis comprehend the theory of cohesion.;---Penelitian ini merupakan sebuah analisis kohesi pada abstrak tesis yang ditulis oleh mahasiswa Strata 1 (S1) program studi Pendidikan Bahasa Inggris di salah satu universitas negeri di Bandung. Abstrak merupakan salah satu elemen penting yang terdapat di dalam tesis. Oleh karena itu, sebuah abstrak harus ditulis sebagai teks yang kohesif, bukan hanya suatu kumpulan kalimat yang tidak berhubungan. Penelitian ini bertujuan untuk mengeksplorasi realisasi cohesive devices dalam abstrak pada beberapa tesis yang ditulis oleh mahasiswa S1 program Pendidikan Bahasa Inggris di suatu universitas negeri di Bandung. Penelitian ini juga mencoba untuk mengungkap kontribusi cohesive devices yang digunakan mahasiswa untuk menulis abstrak yang kohesif. Penelitian ini merupakan penelitian deskriptif yang melibatkan 42 abstrak sebagai data penelitian. Penelitian ini menghasilkan dua penemuan utama. Pertama, cohesive devices yang digunakan dalam abstrak mahasiswa berupa reference, conjunction, substitution, dan lexical cohesion. Reference adalah device yang paling banyak ditemukan di dalam abstrak, yang muncul sebanyak 1156 kali. Kedua, masing-masing device memberikan kontribusi yang signifikan terhadap kohesif atau tidaknya abstrak mahasiswa. Reference berkontribusi dalam melacak penggunaan partisipan dan membantu pembaca untuk menghubungkan satu bagian dari text dengan bagian sebelumnya di dalam teks atau dengan info di luar teks Lexical cohesion juga berkontribusi untuk melacak penggunaan partisipan. Sedangkan, kontribusi conjunction dalam abstrak mahasiswa adalah untuk menghubungkan bagian teks sebelumnya dengan bagian teks sesudahnya secara sistematis. Selain itu, substitution digunakan oleh mahasiswa untuk menghindari pengulangan dalam abstrak. Berdasarkan penemuan tersebut, dapat disimpulnkan bahwa cohesive devices merupakan devices yang penting dalam menulis abstrak yang kohesif. Tanpa devices ini, serangkaian kalimat akan memiliki keterkaitan yang rendah antara satu sama lain dan mungkin tidak dianggap sebagai teks (Halliday dan Hasan, 1976). Oleh karena itu, mahasiswa yang akan menulis abstrak atau tesis secara keseluruhan disarankan untuk memahami teori kohesi.